Observation the swallowing mechanism in elderly patients with pharyngeal dysphagia - Claudia Ximena Campo-Cañar (Revista de la Facultad de Ciencias de la Salud, 2010)
Observation of the swallowing dynamics is an issue that demands close attention by the health professionals involved in the diagnosis and management of patients with dysphagia. This article is a review of the literature aimed to enhance the knowledge regarding the speech therapy assessment of pharyngeal dysphagia in elder adults. The disorder of the swallowing is called dysphagia and it is defined as difficulty swallowing. The dysphagia is often caused by affectation of mechanical or neuromuscular components of the swallowing mechanism. This type of disorder is likely to impact the the oral, pharyngeal and esophageal phases of the swallowing. The speech therapist should take into account assessing aspects such as level of consciousness, vital signs, whether or not the patient is ventilator dependent, means of feeding, if intubated what type of cannula, whether or not the patient uses a speaking valve (if a trach tube is present), nutritional status, the patient’s expressive and receptive language, the anatomical and physiological state of the oral motor structures. When assessing swallowing clinicians should also make sure to develop an adequate beside clinical, voice assessment and videofluoroscopy.